Penerapan Model Student Teams-Achievment Division (STAD) Berbantu Alat Permainan Pecahan Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Matematika Materi Pecahan Semester II Kelas IV SD 2 Padurenan Kecamatan Gebog Kabupaten Kudus - Noor Fatkhiyah (Journal Prakarsa Paedagogia, 2018)
In general, action research aims to improve mathematics learning outcomes with the subject matter of simplifying fractions Elementary School fourth grade students 2 Padurenan Gebog Kudus in the Academic Year 2017/2018. Learning model used is Student Teams-Achievement Division (STAD) with a subject of research students 2 Padurenan Elementary School fourth grade and time studies conducted over three months consisted of two cycles. Each cycle consists of planning, implementation, observation and reflection. Data collection tool using written tests and non-test. While the techniques of data analysis using qualitative analysis techniques. The results showed learning model STAD can improve student learning outcomes. It can be seen from the increase in average student learning outcomes of the initial condition for 55.56 increased to 67.78 in Cycle 1 with a passing grade of 61.11%, and in cycle 2 to 78.33 with a passing grade of 77, 78%.